2017
DOI: 10.1161/circulationaha.116.025582
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Edematous Response of the Human Heart to Myocardial Infarction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(48 citation statements)
references
References 49 publications
(96 reference statements)
2
38
0
Order By: Relevance
“…Furthermore, the same animals were not serially scanned. Most recently, Fernandez-Jimenez and colleagues 13 showed that the bimodal edematous response of the infarct related territory was present in humans as well. However, they used the less robust T2-weighted imaging modality instead for both quantifying the extent of the edema-based area-at-risk and for detecting intramyocardial hemorrhage.…”
Section: Current Controversies In Cmr Imaging Of Stemi Patientsmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, the same animals were not serially scanned. Most recently, Fernandez-Jimenez and colleagues 13 showed that the bimodal edematous response of the infarct related territory was present in humans as well. However, they used the less robust T2-weighted imaging modality instead for both quantifying the extent of the edema-based area-at-risk and for detecting intramyocardial hemorrhage.…”
Section: Current Controversies In Cmr Imaging Of Stemi Patientsmentioning
confidence: 97%
“…There is currently no consensus on the optimal timing for performing the acute CMR scan although 3–5 days 6 and 4–7 days 13 post-PPCI have been proposed.…”
Section: Current Controversies In Cmr Imaging Of Stemi Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of post-reperfusion CMR scans remains an important issue. Most CMR parameters of myocardial function and infarct severity change significantly over time [143][144][145][146]. Therefore, performing CMR very early after PCI (Day 1) leads to a considerable overestimation of IS because of edema and partial volume effect [147].…”
Section: Remaining Challenges and Opportunitiesmentioning
confidence: 99%
“…The interpretation of oedema in MI during life is considered as complicated and controversial today. An initial wave of oedema appears abruptly at reperfusion, significantly attenuated by 24 h and then followed by a second healing-related wave of oedema several days after reperfusion [75]. Post-mortem radiological evaluation of ischemic myocardium is extremely challenging.…”
Section: Resuscitationmentioning
confidence: 99%